MICROSOFT ACCESS-BASED ACCOUNTING SYSTEM DESIGNATED FOR SMALL AND MEDIUM ENTERPRISE DEPOT AIR GALON YOYO - Muhammad Taufik; Clarita Valeria Sugianto (ConCEPt - Conference on Community Engagement Project, 2022)
The accounting conventional method is still applied by Depot Air Galon Yoyo. The Microsoft Access-based Accounting System designated for Small and Medium Enterprise (SME) is a form of community service to help overcome the problems experienced by SMEs in recording or keeping accounting records from the conventional system to software-based accounting. The conventional bookkeeping system can cause inefficiency in time for preparing the financial statements, and do not meet the faithful representation’s criteria. Data for the purpose of designing Microsoft Access-based accounting system were obtained through interview with SME’s owner, and field observation. The outputs generated from the accounting application are bookkeeping administration, and reports. The output of bookkeeping administration includes a list of accounts, a list of suppliers, a list of customers, a list of supplies, a general journal form, a purchase form, a sales form, an inventory adjustment form, and a payable payment form. Output reports include income statements, balance sheets, sales reports, purchase reports, remaining inventory reports, remaining accounts payable reports, statements of changes in capital, and financial position. Relational database can be formed with the output of bookkeeping administration and report output that are interconnected. Thus, the implementation of accounting system helps SME in mitigating errors in recording the amount of inventory, reducing the occurrence of errors in payment of debts by SME to suppliers, and save more time in completing SME’s financial reports so that SME owners can quickly make the right decisions for their business to grow.